Hepatocyte-specific mitogen-activated protein kinase phosphatase 1 in sexual dimorphism and susceptibility to alcohol induced liver injury - Walter, Mary Nancy; Montoya-Durango, Diego; Rodriguez, Walter; Wang, Yali; Zhang, JingWen; Chariker, Julia H.; Rouchka, Eric C.; Maldonado, Claudio; Bennett, Anton; McClain, Craig James; Barve, Shirish; Gobejishvili, Leila (Frontiers in Immunology, 2024)
Background: It is well established that females are more susceptible to the toxic effects of alcohol, although the exact mechanisms are still poorly understood. Previous studies noted that alcohol reduces the expression of mitogen-activated protein kinase phosphatase 1 (MKP1), a negative regulator of mitogen-activated protein kinases (MAPK) in the liver. However, the role of hepatocytespecific MKP1 in the pathogenesis of alcohol-associated liver disease (ALD) remains uncharacterized. This study aimed to evaluate the role of hepatocyte-specific MKP1 in the susceptibility and sexual dimorphism in alcohol-induced liver injury.Methods: C57Bl/6 mice were used in an intragastric ethanol feeding model of alcohol-associated steatohepatitis (ASH). Hepatocyte-specific Mkp1 -/-knockout and (Mkp1 +/+ "f/f" male and female mice were subjected to the NIAAA chronic plus binge model. Primary mouse hepatocytes were used for in vitro studies. Liver RNA sequencing was performed on an Illumina NextSeq 500. Liver injury was evaluated by plasma alanine transaminase (ALT), hepatic ER stress and inflammation markers.Statistical analysis was carried out using ANOVA and the unpaired Student's t-test.Results: ASH was associated with the severe injury accompanied by increased endoplasmic reticulum (ER) stress and significant downregulation of Dusp1 mRNA expression. In vitro, ethanol treatment resulted in a time-dependent decrease in Dusp1 mRNA and protein expression in primary hepatocytes in both males and females; however, this effect was significantly more pronounced in hepatocytes from females. In vivo, female mice developed more liver injury in a chronic plus binge model which was accompanied by a significant decrease in liver Dusp1 mRNA expression. In comparison, liver Dusp1 was not changed in male mice, while they developed milder injury to alcohol.Mkp1 deletion in hepatocytes led to increased alcohol induced liver injury, ER stress and inflammation t in both sexes.Hepatocyte Mkp1 plays a significant role in alcohol induced liver injury. Alcohol downregulates Mkp1 expression in hepatocytes is in a sex dependent manner and could play a role in sexual dimorphism in increased female susceptibility to alcohol.